A Review of Virtual Reality for English Language Learning in Higher Education - Febriyanti Utami; Yudi Wili Tama; Ilza Mayuni (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
Virtual Reality (VR) has seen increasing popularity in the twenty-first century, including in the field of language learning. Considerable studies on VR have explored mainly its advantages and disadvantages for language learning. However, a gap existed about the influential factors considered in incorporating VR technology, particularly for English language learning in higher education settings. Therefore, this study aimed to 1) identify important factors that influence the application of VR technology; 2) provide a systematic review of literature on the implementation categories of VR; and 3) discuss the challenges and opportunities of VR use for English language learning in higher education. A Systematic Literature Review (SLR) was conducted by reviewing articles retrieved from 2018 to 2023 using a digital database library and filtered systematically using exclusion and inclusion criteria. The result showed that advanced technology, teaching and learning facilitation, and effectiveness in language learning were three major factors influencing VR implementation, which were categorized under three key elements: models, frameworks, or approaches. The study also found out that the cost of procurement and maintenance as well as lack of technical skills were the main challenges of VR use; however, the technology offered opportunities such as reducing learners’ anxiety, increasing their motivation, facilitating immersive and interactive learning experiences, developing English skills, and improving the quality of language education. It is suggested that further research and development efforts should focus on overcoming the challenges to unlock the full potential of VR technology in education